THE PLACE OF THE ARTISTIC WORD IN LANDSCAPE DESCENT (Universal International Scientific Journal, 2026)
This article scientifically analyzes the specific features of the linguistic factor in the creation of landscape images in the work "Boburnoma". The study comprehensively covers the lexical, syntactic and stylistic means used by Zahiriddin Muhammad Babur in creating landscapes. In particular, short and clear sentences, a simple, fluent narrative method, a principle of imagery free from excessive silence, and forms of expression based on realistic and objective observation are indicated as the main factors ensuring the naturalness and vitality of landscape images.
Keywords: word; allegory; “Baburnama”